2012
DOI: 10.1172/jci64837
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency-causing mutation defines CD16 in spontaneous NK cell cytotoxicity

Abstract: The Fc receptor on NK cells, FcγRIIIA (CD16), has been extensively studied for its role in mediating antibodydependent cellular cytotoxicity (ADCC). A homozygous missense mutation in CD16 (encoding a L66H substitution) is associated with severe herpesvirus infections in rare patients. Here, we identified a new patient with this CD16 mutation and compared the patient's NK cells to those of the originally reported patient. Patients with the L66H mutation had intact ADCC, but deficient spontaneous NK cell cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
141
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 41 publications
1
141
0
2
Order By: Relevance
“…IL-2 (Roche) was added at a concentration of 125 U/mL to YTS cells or 1000 U/mL to eNK cells, only after the time indicated; 100 ng/mL IL-10 (Serotec) was added to YTS cells at time zero. Western blot analysis for pSrc and Myosin II A was performed as described 26 using a polyclonal antibody directed against phospho Src Y416 (Cell Signaling).…”
Section: Inhibitors and Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-2 (Roche) was added at a concentration of 125 U/mL to YTS cells or 1000 U/mL to eNK cells, only after the time indicated; 100 ng/mL IL-10 (Serotec) was added to YTS cells at time zero. Western blot analysis for pSrc and Myosin II A was performed as described 26 using a polyclonal antibody directed against phospho Src Y416 (Cell Signaling).…”
Section: Inhibitors and Cytokinesmentioning
confidence: 99%
“…26 Live cell confocal microscopy GFP-tubulin-expressing YTS were incubated with 5 mM LysoTracker Red DND-99 (Molecular Probes) for 30 minutes at 37°C, washed, and added to 721.221 cells that had been adhered to DT dishes (Bioptechs) precoated with antibodies against CD48 (BD). 3 Conjugates were imaged in z-axis planes containing the MTOC using a Zeiss Z1 microscope with Yokogawa CSU10 spinning disc, 633 1.43 NA objective, and solid-state 488-and 561-nm lasers.…”
mentioning
confidence: 99%
“…To corroborate these observations, we tested two different cell lines for which the main receptors are well-defined in direct killing assays. In K562 cells, the killing of which is mostly NKG2D-dependent, killing was highly similar between NKs from the patient and the NKs from healthy donors, while the killing of 1106mel cells that is CD16 dependent [11][12][13] showed that the patient's NK cells are superior effectors when CD16 is directly engaged.…”
Section: Introductionmentioning
confidence: 91%
“…Pored toga što učestvuje u ADCC, pokazano je da CD16 može da se direktno veže za ćelije tumora i da time dovodi do citototoksične aktivnosti NK ćelija (Mandelboim et al,1999;Grier et al, 2012). CD16 receptor je nekovalentno vezan sa homodimerom koga čine FcRγ lanci ili homodimerom TCRζ lanaca ili heterodimerom FcRγ i TCRζ koji su značajni u signalnom putu CD16 receptora.…”
Section: Cd16unclassified
“…Značaj CD16 kao molekula koji ima ulogu u citotoksičnoj aktivnosti NK ćelija je pokazan još 1999. godine (Madelboim et al, 1999), mada tada tačan mehanizam kojim CD16 učestvuje u citotoksičnoj aktivnosti NK ćelija nije pokazan i nisu identifikovani njegovi ligandi za koje se on vezuje pri formiranju imunološke sinapse. Međutim, novija istraživanja su pokazala da svoju ulogu u NK ćelijskoj citotoksičnosti CD16 receptor ispoljava cis interakcijom sa CD2 adhezionim molekulom što može da dovede do fosforilacije i aktivacije ζ lanca TCR i do sledstve ne NK ćelijske citotoksičnosti (Grier et al, 2012). Osim toga, pokazano je da prisustvo CD2 adhezionog molekula na NK ćelijama je neophodno za NK-citotoksičnost prema većini tumorskih ćelijskih linija melanoma (Casado et al, 2009) NK ćelijama nakon tretmana se povećava kod obe grupe limfnih čvorova pod uticajem oba ispitivana citokina.…”
Section: Diskusijaunclassified